Analisis Kesiapan Implementasi Rekam Medis Elektronik Menggunakan Instrumen CAFP (Californias Academy of Family Physician) - Hazimah, Isyroqul; Khasanah, Lina (Jurnal Informasi Kesehatan Indonesia (JIKI), 2024)
A paradigm shift that combines digital and physical technology can create better resources, especially technology in the health sector which is experiencing very rapid progress. Concrete evidence of digital transformation in the health sector is the existence of an information system in the form of Electronic Medical Records (RME). California Academy of Family Physician (CAFP) is an instrument used to analyze the level of readiness of EMR, CAFP was formed by the state medical organization or commonly called the California Academy of Family Physicians. This instrument has a description of the assessment in the form of a narrative and has scores grouped in 3 categories. The study was conducted with quantitative descriptive methods and cross sectional approaches. The purpose of this study is to develop the CAFP instrument into Indonesian form and compiled into a questionnaire that is tested for validity and reliability. Based on the results of the study, it shows that the factors that affect the readiness of RME implementation are management capacity, financial and budgetary capacity, operational capacity, technological capacity, and organizational alignment. The results of the development of the questionnaire obtained 27 questions. The results of the validity test showed that all components of readiness in the study were valid where r-count>r-table and Cronbach's alpha value was 0.924 which stated that the questionnaire was reliable. The questionnaire model that has been developed can be used to measure the level of readiness to implement EMR in health care facilities. Keywords: RME, Puskesmas, Validity, Reliability, Readiness